2020
DOI: 10.3389/fimmu.2019.03125
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pathogenic Th17 Cells Is Negatively Regulated by Let-7 MicroRNAs in a Mouse Model of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a disabling demyelinating autoimmune disorder of the central nervous system (CNS) which is driven by IL-23-and IL-1β-induced autoreactive Th17 cells that traffic to the CNS and secrete proinflammatory cytokines. Th17 pathogenicity in MS has been correlated with the dysregulation of microRNA (miRNA) expression, and specific miRNAs have been shown to promote the pathogenic Th17 phenotype. In the present study, we demonstrate, using the animal model of MS, experimental autoimmune enceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 68 publications
(118 reference statements)
3
47
0
Order By: Relevance
“…We then computed the correlation between the CSF levels of each inflammatory protein and let-7b-5p. Importantly, as reported in Table 2 and Figure 3A', we observed that let-7b-5p positively correlated with all members of the Cluster 1, and negatively correlated with most inflammation-related factors belonging to the Cluster 2, including also experimentally-validated targets or pathways of let-7 family, like IL6 [65][66][67][68], IL10 [15,69] and IL17 pathway [12]. To further investigate the involvement of let-7b-5p in MS pathology, we compared the miRNA levels in the CSF between control subjects and the main cohort of patients with MS. We observed a highly variable expression among the patients respect to control subjects (Ctr: n = 20; MS: n = 166; Mann-Whitney test, p > 0.05) ( Figure 4A).…”
Section: Let-7b-5p Is a Putative Anti-inflammatory Regulator Of The Csupporting
confidence: 72%
“…We then computed the correlation between the CSF levels of each inflammatory protein and let-7b-5p. Importantly, as reported in Table 2 and Figure 3A', we observed that let-7b-5p positively correlated with all members of the Cluster 1, and negatively correlated with most inflammation-related factors belonging to the Cluster 2, including also experimentally-validated targets or pathways of let-7 family, like IL6 [65][66][67][68], IL10 [15,69] and IL17 pathway [12]. To further investigate the involvement of let-7b-5p in MS pathology, we compared the miRNA levels in the CSF between control subjects and the main cohort of patients with MS. We observed a highly variable expression among the patients respect to control subjects (Ctr: n = 20; MS: n = 166; Mann-Whitney test, p > 0.05) ( Figure 4A).…”
Section: Let-7b-5p Is a Putative Anti-inflammatory Regulator Of The Csupporting
confidence: 72%
“…MS is a chronic inflammatory disease of the central nervous system (CNS). Th17 pathogenicity in MS has been correlated with the dysregulation of the expression of microRNAs (miRNAs), and specific miRNAs promote the pathogenic phenotype [ 138 ]. In MS, autoreactive Th17 cells, generated by IL-23 and IL-1β, migrate to the CNS and cross the blood–brain barrier.…”
Section: T Helper 17 Cells (Th17)mentioning
confidence: 99%
“…In MS, autoreactive Th17 cells, generated by IL-23 and IL-1β, migrate to the CNS and cross the blood–brain barrier. In encephalitogenic Th17 cells, the Bhlhe40 transcription factor, which is induced by IL-1β signalling, positively regulates the secretion of GM-CSF and consequently, GM-CSF-stimulated glial and dendritic cells reinforce the differentiation and maintenance of pathogenic Th17 cells, by secreting IL-6 and IL-23 [ 138 ].…”
Section: T Helper 17 Cells (Th17)mentioning
confidence: 99%
“…Therefore, the future functional characterization of rEg.P29 may further the understanding of the molecular mechanism associated with rEg.P29. MicroRNAs are critical for a broad range of biological processes, including T cell homeostasis and activation [16,18,30]. Over recent years, accumulating data have also shown that miRNAs are important for modulating CD4 + T cell differentiation and plasticity [31].…”
Section: Discussionmentioning
confidence: 99%